ANALISIS PERAN MODEL PEMBELAJARAN DALAM MENINGKATKAN KUALITAS STRATEGI PEMBELAJARAN - Muhammad Antariksa Adnan Nugraha; Ziyadah El Fadllilah; Fina Nikmatul Kamelia; Putri Nurul Aziah; Nur Laila Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the widespread misunderstanding of the distinction between learning strategies and learning models, approaches, methods, and techniques. A proper understanding of these concepts is crucial for creating an effective learning process. This study aims to examine the basic concept of learning strategies and identify their differences from other learning components. The method used is a literature review, examining various relevant theoretical sources. The results indicate that learning strategies are general plans for learning activities that include objectives, materials, methods, media, and evaluation. Learning strategies have various classifications, such as based on the roles of teachers and students and the method of delivering material, such as expository, heuristic, deductive, and inductive strategies. Furthermore, learning strategies have a broader scope than models, approaches, methods, and techniques. Models serve as a conceptual framework, approaches as a basis for perspective, methods as a means of delivering material, and techniques as operational steps in implementing learning. This indicates that strategies are the primary guide in the entire learning process. Therefore, a clear understanding of learning strategies and their differences from other concepts is essential to improving the quality of learning.